Taking decision general theory and its application in the medical assistance field (I). - Luis Alberto Corona Martínez (Medisur)
Decision making is a necessary element in the medical work. This article is a part of a series of articles that is aimed at divulging some theoretical aspects about decision making and their concrete application in the medical assistance. This paper analyses the classic (rational) and behavioural theories in decision making.